2013
DOI: 10.3389/fpsyg.2013.00841
|View full text |Cite
|
Sign up to set email alerts
|

The movements made by performers in a skilled quartet: a distinctive pattern, and the function that it serves

Abstract: When people perform a task as part of a joint action, their behavior is not the same as it would be if they were performing the same task alone, since it has to be adapted to facilitate shared understanding (or sometimes to prevent it). Joint performance of music offers a test bed for ecologically valid investigations of the way non-verbal behavior facilitates joint action. Here we compare the expressive movement of violinists when playing in solo and ensemble conditions. The first violinists of two string qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 40 publications
6
78
0
2
Order By: Relevance
“…the lower voice) tended to lag at NB and NE, but precede at OF. Furthermore, these contrasting patterns of leader-follower relationships show bidirectional adaptations between performers rather than a clear separation of roles, corroborating previous studies analysing the synchronization of onsets among string quartets (29)(30)(31)(32). This also suggests that the reciprocal and iterative adjustments are not limited to the attack of the note, but to the full performance of notes, including NB, NE and OF in addition to ON.…”
Section: Discussionsupporting
confidence: 89%
“…the lower voice) tended to lag at NB and NE, but precede at OF. Furthermore, these contrasting patterns of leader-follower relationships show bidirectional adaptations between performers rather than a clear separation of roles, corroborating previous studies analysing the synchronization of onsets among string quartets (29)(30)(31)(32). This also suggests that the reciprocal and iterative adjustments are not limited to the attack of the note, but to the full performance of notes, including NB, NE and OF in addition to ON.…”
Section: Discussionsupporting
confidence: 89%
“…In musical performance, a performer's body movements and gestures can convey a range of meaningful information to audiences and co-performers alike, including emotional expression (Castellano, Mortillaro, Camurri, Volpe, & Scherer, 2008;Dahl & Friberg, 2007;Davidson, 1993Davidson, , 1994 and phrasing (Juchniewicz, 2008;Vines, Krumhansl, Wanderley, & Levitin, 2006), as well as musical ideas and timing (Glowinski et al, 2013;Goebl & Palmer, 2009;Williamon & Davidson, 2002). The salience of visual kinematic information (i.e., visual information about performers' body movements and gestures) for an observer's perception and experience of a musical performance has been widely documented (e.g., Chapados & Levitin, 2008;Davidson, 1993;Tsay, 2013;Vines, Krumhansl, Wanderley, Dalca, & Levitin, 2011;Vines et al, 2006), and a recent meta-analysis by Platz and Kopiez (2012) revealed that, compared to audio-only presentations, audiovisual information has a moderate effect on participants' evaluations of a musical performance.…”
Section: Usic Is An Inherently Multisensorymentioning
confidence: 99%
“…This feature is regarded as an indicator of the degree of synchronisation between a pair of performers in a team. Especially in the field of music and dance, synchronisation is used to measure the level of collaboration and entitativity of a group of people (that is, their tendency to act as a single entity) performing a joint activity [39][31]. In the proposed system, the synchronisation between a pair of performers is computed starting from the bpm they are expressing by moving their mobile devices.…”
Section: Social Features Extractionmentioning
confidence: 99%